PENGARUH RELOKASI, LAMA USAHA DAN MODAL USAHA TERHADAP PENDAPATAN UMKM (STUDI KASUS PEDAGANG SHELTER MANAHAN SOLO) - Nabilah Lufhi Widiyanti; Dewi Ika Octavia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine the effect of relocation, length of business, business capital on MSME income at the Manahan Solo shelter. This type of research is qualitative research. The population in this study were 120 traders at the Manahan Solo shelter. The sample in this study was determined using a saturated sampling technique. Data collection using questionnaires through validity and reliability tests. The data analysis technique uses multiple regression. The research results show that relocation has a significant effect on income, length of business has a significant effect on MSME income, business capital has a significant effect on income. The results of the relocation F test, length of business and business capital have a significant effect on MSME income.